Fenomena Judi Online di Kalangan Generasi Muda - Riski Kamila Juliani; Muhammad Satria; Reza Mauldy Raharja; Wika Hardika Legiani (Pusat Riset dan Inovasi Nasional, 2024)
Online gambling games are popular among teenagers nowadays. This is caused by very sophisticated technological advances, socio-economic pressures, and the role of social media as an advertising platform. This research aims to understand the reasons why the younger generation plays online gambling and solve the problems of this case. In collecting data, researchers obtained data through observation and interviews. The results of this research explain the factors of playing online gambling such as environmental, cognitive and perception factors. This case has an impact on finances (material values), vital values, spiritual values ​​(mental health and social relationships). Playing online gambling games is caused by technological accessibility, socio-economic pressures, lack of public awareness about the laws and risks of online gambling.